Kampen mot sunket: Kaos och ordning i retrovärlden - Brembeck, Helene (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
A basic task for shop owners on the new market for retro and vintage is to do away with associations to mess and squalor. This article shows how this transformation of secondhand objects and shops from scruffy flea markets to trendy boutiques is made by the use of strategies of removing, shop making and creating flows and channels. Theoretical inspiration is drawn from studies of the “qualification” of goods and of the managing of overflows. The field is central Gothenburg; the methods are ethnographic including onsite observations in 22 shops, interviews with shopkeepers and staff, photo and online documentations.